Tiny CSS projects - Dowden, Martine; Gearon, Michael (Manning Publications, 2023)
CSS is a must-know language for all web developers. In this practical book, you'll explore numerous techniques to improve the way you write CSS as you build 12 tiny projects. In Tiny CSS Projects you'll build twelve exciting and useful web projects including: A loading screen created by styling SVG graphics A responsive newspaper layout with multiple columns Animating social media buttons with pseudo-elements Designing layouts using CSS grids Summary cards that utilize hover interactions Styling forms to make them more appealing to your users The projects may be tiny, but the CSS skills you'll learn are huge! Tiny CSS Projects teaches you how to make beautiful websites and applications by guiding you through a dozen fun coding challenges. You'll learn important skills through hands-on practice as you tinker with your own code and make real creative decisions about the projects you're building. You'll rapidly master the basics and then press on into CSS's exciting layout features including grid and flexbox, animations, transitions, and media queries. About the Technology Don't settle for boring web pages! With Cascading Style Sheets you can control color, layout, and typography to make your sites both functional and beautiful. CSS is an essential skill for web developers and designers. This book will help you get started the right way. About the Book Tiny CSS Projects builds your CSS skills by guiding you through 12 creative mini-projects. Each interesting challenge starts with a downloadable HTML skeleton. As you flesh it out with your own design ideas, you'll master CSS concepts like transitions, layout, and styling forms, and explore powerful features including Flexbox and Grid. All the skills you'll learn are easy to transfer to full-size applications. When you finish, you'll have an exciting portfolio of designs ready to go for your next project. What's Inside Transitions and animations using keyframes Layout techniques including Grid and Flexbox Styling form elements including radio buttons Embedding fonts and typography-related styles Conditional styling using pseudo-elements and media queries About the Reader For readers who know the basics of HTML and frontend development. No previous experience with CSS is required. About the Authors Martine Dowden is an author, speaker, and award-winning CTO. Michael Gearon is a user experience designer and frontend developer who has worked with many well-known brands. Quotes A great project-based approach to learning CSS with something for all skill levels. - Joe Attardi, author of Modern CSS An excellent resource! Written in simple language with plenty of applicable examples. This book proves that it is never too late to learn, even after decades of experience. I highly recommend it! - Joseph Del Vecchio, Heritage Environmental Services Clear and concise so it's easy to understand...makes learning engaging and fun. The instructions and code are well-organized and easy to follow. - Md. Zahid Hossain, Webapp Solutions.
Online resource; title from title details screen (O'Reilly, viewed February 05, 2024)
Keywords: Cascading style sheets; Web site development; Feuilles de style en cascade; Sites Web; Développement; Audiobooks; Livres audio